The immunostimulant OM-85 BV prevents wheezing attacks in preschool children - Razi, Cem Hasan; Harmancı, Koray; Abacı, Ayhan; Özdemir, Osman; Hızlı, Şamil; Renda, Rahime; Keskin, Fersin (Journal of allergy and clinical immunology, 2010)
No reagents have been shown to be effective in preventing wheezing attacks provoked by acute respiratory tract illnesses (ARTIs) in preschool children. New therapeutic agents and preventive strategies are needed. We assessed the effect of OM-85 BV (Broncho-Vaxom; OM Pharma, Geneva, Switzerland) in preventing ARTI-provoked wheezing attacks in preschool children with recurrent wheezing. A randomized, double-blind, placebo-controlled, parallel-group study was carried out between August 2007 and September 2008. The study included 75 children with recurrent wheezing who were 1 to 6 years old. Participants were randomly assigned to groups given either OM-85 BV or a placebo (1 capsule per day for 10 days each month for 3 consecutive months) at the start of the trial. Participants were followed for 12 months, which included the administration period of the test article. Subjects given OM-85 BV had a lower rate of wheezing attacks. The cumulative difference in wheezing attacks between the 2 groups was 2.18 wheezing attacks per patient in 12 months; there was a 37.9% reduction in the group given OM-85 BV compared with the group given placebo (P < .001). Stepwise multiple (linear) regression analysis showed that the main difference between the OM-85 BV and placebo groups was a reduction the number of ARTIs ( R = −0.805, P < .001). The duration of each wheezing attack was 2 days shorter in the group given OM-85 BV than in the group given placebo ( P = .001). Administration of OM-85 BV significantly reduced the rate and duration of wheezing attacks in preschool children with ARTIs.